Interleukin-12p40 in the spinal fluid as a biomarker for clinically isolated syndrome. (January 2014) - Orbach, Rotem; Gurevich, Michael; Achiron, Anat
Background: The cerebrospinal (CSF) constitutes a specific immune micro-environment to the central nervous system, thus it may contain specific biomarkers involved in the pathogenesis of multiple sclerosis (MS). Objectives: We aimed to study a large array of inflammatory CSF biomarkers in patients with suspected MS to recognize potential early diagnostic markers. Methods: CSF samples were obtained from 115 patients who presented with neurological symptomatology suggestive of MS as follows: clinically isolated syndrome (CIS) = 49, relapsing–remitting multiple sclerosis (RRMS) = 29, and other neurologic disorders (OND) = 37. Protein expression profiles of 30 inflammatory biomarkers were measured by multiplex Luminex bead assay and further analyzed by group comparison statistics, correlation studies and receiver-operating characteristic (ROC) analysis. Results: Interleukin-12 subunit p40 (IL12p40) demonstrated a significant differential expression pattern between the groups (CIS vs OND: p = 1.17*10 −7 ; RRMS vs OND: p = 4.98*10 −5 ), with higher levels in CIS and RRMS patients. ROC analysis demonstrated excellent diagnostic performance of IL12p40 for discrimination between CIS and OND patients (area under the curve = 0.87 (95% CI 0.78–0.93), p = 0.0001). No associations were found with disease activity or severity measures. Conclusions: An increased IL12p40 level characterizes the CSF of MS patients and appears to be helpful in identifying CIS and OND patients early in the process of clinical diagnostic assessment.